Numerical Study of Multivortex Regulation in Curved Microchannels with Ultra-Low-Aspect-Ratio - Shaofei Shen; Mengqi Gao; Fangjuan Zhang; Yanbing Niu (Micromachines, 2021)
The field of inertial microfluidics has been significantly advanced in terms of application to fluid manipulation for biological analysis, materials synthesis, and chemical process control. Because of their superior benefits such as high-throughput, simplicity, and accurate manipulation, inertial microfluidics designs incorporating channel geometries generating Dean vortexes and helical vortexes have been studied extensively. However, existing technologies have not been studied by designing low-aspect-ratio microchannels to produce multi-vortexes. In this study, an inertial microfluidic device was developed, allowing the generation and regulation of the Dean vortex and helical vortex through the introduction of micro-obstacles in a semicircular microchannel with ultra-low aspect ratio. Multi-vortex formations in the vertical and horizontal planes of four dimension-confined curved channels were analyzed at different flow rates. Moreover, the regulation mechanisms of the multi-vortex were studied systematically by altering the micro-obstacle length and channel height. Through numerical simulation, the regulation of dimensional confinement in the microchannel is verified to induce the Dean vortex and helical vortex with different magnitudes and distributions. The results provide insights into the geometry-induced secondary flow mechanism, which can inspire simple and easily built planar 2D microchannel systems with low-aspect-ratio design with application in fluid manipulations for chemical engineering and bioengineering.